Teaching Counselling Amid the Evolving Evidentiary Landscape - Nuttgens, Simon; Anderson, Murray S.; Brown, Emeleigh D. (Canadian Journal of Counselling and Psychotherapy, 2021)
Historically, professional counselling has been mired by “theory wars” involving proponents going to great lengths to prove (either through research or through rhetoric) that their approach was superior to others. This, not surprisingly, led to rancour and division within professional counselling and a form of camp mentality among model adherents. This paper offers an innovative approach to teaching models of counselling that counters such tendencies. The impetus for this approach stems from a robust and growing body of research indicating that counselling models, although often revered among model adherents and assumed to be the sine qua non of effective counselling, now appear to play a smaller role within the therapeutic enterprise. While few (including the present authors) would argue that counselling models are unnecessary, the various lines of research outlined in this paper compel counsellor educators to rethink how counselling models ought to be taught to graduate-level counselling students.